2019
DOI: 10.1002/job.2343
|View full text |Cite
|
Sign up to set email alerts
|

Leader‐signaled knowledge hiding: Effects on employees' job attitudes and empowerment

Abstract: Summary The authors introduce the concept of leader‐signaled knowledge hiding (LSKH) and conduct two studies observing what happens when leaders signal employees that knowledge hiding (KH) is practiced, tolerated, and expected. Social learning theory provides the basis for predicting that LSKH encourages subordinates to hide knowledge, even though they suffer from negative job attitudes in reaction. In Study 1, data measured at two time points (N = 1,162) shows that LSKH positively predicts KH among subordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 104 publications
(176 reference statements)
10
141
0
Order By: Relevance
“…When playing dumb, the hider pretends not to have the requested knowledge. Evasive hiding and playing dumb involve deception, while rationalized hiding rather does not (e.g., Offergelt et al, 2019;Zhao et al, 2016). Hence, one can conclude that rationalized hiding shows less overlap with CWBs and is, thus, less likely to play a role in negative social interactions at work.…”
Section: A Transactional Perspective On Knowledge Hiding Interpersonmentioning
confidence: 96%
“…When playing dumb, the hider pretends not to have the requested knowledge. Evasive hiding and playing dumb involve deception, while rationalized hiding rather does not (e.g., Offergelt et al, 2019;Zhao et al, 2016). Hence, one can conclude that rationalized hiding shows less overlap with CWBs and is, thus, less likely to play a role in negative social interactions at work.…”
Section: A Transactional Perspective On Knowledge Hiding Interpersonmentioning
confidence: 96%
“…Offergelt, Spörrle, Moser, and Shaw () explain subordinate knowledge hiding by introducing and measuring the concept of leader‐signaled knowledge hiding. On the basis of social learning theory and role modeling, they define leader‐signaled knowledge hiding as the extent to which subordinates perceive their leader to practice, tolerate, and expect knowledge hiding.…”
Section: Articlesmentioning
confidence: 99%
“…For example, some studies (e.g., Jiang et al, ) examine knowledge hiding as a holistic construct, whereas others consider the roles of each facet separately (e.g., Zhu et al, ). Likewise, two studies (i.e., Offergelt et al, ; Zhao et al, ) explore the role of leaders and leadership in predicting knowledge hiding, whereas the other articles focus primarily on interemployee dyadic interactions. Whereas one study examines knowledge sharing as well as knowledge hiding (i.e., Gagné et al, ), the other studies consider knowledge hiding exclusively.…”
Section: Future Directionsmentioning
confidence: 99%
“…Such reciprocity loops were also found among 336 students and employees in Slovenia (Cerne, Nerstad, Dysvik, & Skerlavaj, 2014). As a final set of examples of negative behaviors, various supervisory behaviors were found influential: abusive supervision predicted knowledge hiding in a sample of 364 Pakistani telecommunications employees (Jahanzeb, Fatima, Bouckenooghe, & Bashir, 2019), despotic leadership was associated with knowledge hoarding in a sample of 334 Pakistani telecom employees (Sarwar, Khan, & Mujtaba, 2017), and in a range of Austrian and German companies, it was found that leaders’ actively tolerating or even showing hiding behavior prompted employee knowledge withholding among 2331 respondents (Offergelt, Spörrle, Moser, & Shaw, 2018).…”
Section: Empirical Review and Integrative Frameworkmentioning
confidence: 99%